Hypogyrification and its association with cognitive impairment in children with 22q11.2 deletion Syndrome: A preliminary report. (30th March 2019) - Lutz, Olivia; Lizano, Paulo; Mothi, Suraj Sarvode; Joseph, Adam; Tandon, Neeraj; Ormston, Leighanne; Hooper, Stephen; Keshavan, Matcheri; Shashi, Vandana
Highlights: There is hypogyrification in medial frontal and parietal cortex in 22q11.2 deletion syndrome. Gyrification shows relationships with cognition in 22q11.2 deletion syndrome. No relationships were observed in controls. Abstract: 22q11.2 Deletion Syndrome (22qDS) is a neurogenetic disorder resulting in cognitive deficits and hypogyrification, but relationships between these processes have not been established. 22qDS youth and healthy controls (HC) were administered a battery of cognitive tasks. Gyrification measurements were extracted from structural T1 scans using Freesurfer, contrasted between groups, and correlated to cognition. Data was adjusted for age, sex, socio-economic status and intracranial volume. 22qDS displayed significant hypogyrification which was associated with poorer executive functioning and verbal learning in orbitofrontal and anterior cingulate cortex. Our preliminary findings identified neurodevelopmental deficits in 22qDS shown by hypogyria, which relate to cognitive impairments.